Seasonality and depth distribution of the abundance and activity of ammonia oxidizing microorganisms in marine coastal sediments (North Sea) - Lipsewers, Yvonne A.; Bale, Nicole J.; Hopmans, Ellen C.; Schouten, Stefan; Sinninghe Damsté, Jaap S.; Villanueva, Laura (Frontiers in Microbiology, 2014)
Microbial processes such as nitrification and anaerobic ammonium oxidation (anammox) are important for nitrogen cycling in marine sediments. Seasonal variations of archaeal and bacterial ammonia oxidizers (AOA and AOB) and anammox bacteria, as well as the environmental factors affecting these groups, are not well studied. We have examined the seasonal and depth distribution of the abundance and potential activity of these microbial groups in coastal marine sediments of the southern North Sea. This was achieved by quantifying specific intact polar lipids (IPLs) as well as the abundance and gene expression of their 16S rRNA gene, the ammonia monooxygenase subunit A (amoA) gene of AOA and AOB, and the hydrazine synthase (hzsA) gene of anammox bacteria. AOA, AOB and anammox bacteria were detected and transcriptionally active down to 12 cm sediment depth. In all seasons, the abundance of AOA was higher compared to the AOB abundance suggesting that AOA play a more dominant role in aerobic ammonia oxidation in these sediments. Anammox bacteria were abundant and active even in oxygenated and bioturbated parts of the sediment. The abundance of AOA and AOB was relatively stable with depth and over the seasonal cycle, while anammox bacteria abundance and transcriptional activity were highest in August. North Sea sediments thus seem to provide a common, stable, ecological niche for AOA, AOB and anammox bacteria.